Development of people's institution in joint forest management: Assumptions, realities and opportunities - Das, P.K. (2003)
Joint Forest Management has emerged as a new strategy for popular participation in forest management through micro-institutional solutions. The experiment has been introduced in various states with varying degree of success. Efforts are afoot to create a space for the local populace, mostly through their local representatives, to participate in this innovative scheme. This article enumerates the available institutional options for strengthening protection and management activities. Trust building measures between local institutions, NGOs and administration and the reduced dependence on forest bureaucracy of this venture. It calls for a greater financial stability and commitment from all concerned to impact sustenance to the mechanism. - Reproduced.
Keywords: Forest management